GAMBARAN PENGETAHUAN TENTANG KEPUTIHAN PADA SISWI SMA DI KABUPATEN OKU SELATAN TAHUN 2016 - Yuhemy Zurizah Yuhemy Zurizah (STIKes Budi Mulia Sriwijaya, 2016)
ABSTRAK Flour Albous is the liquid that comes out of the vagina is not excessive blood. According to the World Health Organization (WHO) research on reproductive health Data show that 75 women in the world are experiencing vaginal discharge is normal and 45 of them may experience abnormal vaginal discharge. Vaginal discharge is caused by some common factor, among other personal hygiene which is less good, stress, drug use, wearing tight underwear, rinse the genitals from the wrong direction, did not immediately replace the pads when the menstruation, and a dirty sanitary environment. The design of this research is a survey with cross sectional approach analytic where the independent variables (understanding, messes, symptoms, causes, complications, and cope, prevent vaginal discharge)and the dependent variable (an overview knowledge on students about whiteness) collected within 2 days. He knew an overview knowledge of whiteness on the HIGH SCHOOL students in the County's southern OKU 2016. This population is all 3rd grade HIGH SCHOOL students in the County's southern OKU 2016. Samples of penelian this is a 3rd grade HIGH SCHOOL students in the South 2016dan OKU taken total engineering population, methods of sampling by disseminating a questionnaire with the amount of 150 respondents. Univarat analysis results showed that respondents found out about understanding whiteness good of 79 respondents (52,6%) while less knowledge of 71 respondents (47,4%), response based on the knowledge of the various good whiteness 112 respondents (74,6%) and while less knowledge i.e. 38 respondents (25,4%). respondents to the investigation of knowledge about signs of vaginal discharge either 95 respondents (63,4%) and while less knowledge i.e. 55 respondents (36,6%) respondents based on the cause of vaginal discharge either 60 respondents (40%) and while less knowledge i.e. 90 respondents (60%),reponden based on knowledge about overcoming good whiteness 62 respondents (41,3%) and while less knowledge i.e. 88 respondents (58,7%),respondents to the investigation of the knowledge of good whiteness complications 78 respondents (52%) and while less knowledge i.e. 72 respondents (48%), and the respondent investigation knowledge how to prevent vaginal discharge either 52 respondents (34,6%) and while less knowledge i.e. 98 respondents (65,4%). Keputihan adalah cairan yang keluar berlebihan dari vagina bukan merupakan darah. Menurut World Health Organization (WHO) Data penelitian tentang kesehatan reproduksi menunjukan bahwa 75% perempuan di dunia mengalami keputihan normal dan 45% diantaranya dapat mengalami keputihan abnormal.Keputihan disebabkan oleh beberapa faktor umum, antara lain personal hygiene yang kurang baik, stress, penggunaan obat-obatan, memakai pakaian dalam yang ketat, membilas alat kelamin dari arah yang salah, tidak segera mengganti pembalut saat menstruasi, dan lingkungan sanitasi yang kotor.Desain penelitian ini adalah survey analitik dengan pendekatan cross sectional dimana variabel independen (pengertian, macam-macam, gejala, penyebab, mengatasi, komplikasi, dan mencegah keputihan) dan variable dependen (gambaran pengetahuan pada siswi tentang keputihan) dikumpulkan dalam waktu 2 hari. Diketahuinya gambaran pengetahuan tentang keputihan pada siswi SMA DI Kabupaten OKU SelatanTahun 2016. Populasi ini adalah semua kelas 3 siswi SMA DI Kabupaten OKU Selatan Tahun 2016. Sampel penelian ini adalah kelas 3 siswi SMA DI Kabupaten OKU Selatan Tahun 2016dan diambil metode teknik total populasi, pengambilan sampel ini dengan cara menyebarkan kuesioner dengan jumlah 150 responden. Hasil analisis univarat menunjukan responden yang mengetahui tentang pengertian keputihan baik sebesar 79 responden (52,6%), Respon berdasarkan pengetahuan tentang macam-macam keputihan baik 112 responden (74,6%) dan berdasarkan pengetahuan tentang mengatasi keputihan baik 62 responden (41,3%) dan responden berdasarakan pengetahuan cara mencegah keputihan baik 52 responden (34,6%)